Architecting resilient systems - Jackson, Scott (Hoboken, New Jersey John Wiley & Sons, Inc., 2025)
Resilient systems safeguard society through the preservation of resources and maintaining clean energy, air, water and supply chains. Resilient systems are able to resist environmental stresses due to climate change, natural disasters or disease outbreaks that impact the health and well-being of society"
Includes index.
Keywords: Reliability (Engineering); Systems engineering; System safety; Industrial safety